Physical test of stainless steel 316 between different manufactures - Zaitul Aqmal, Mohd Asri (2013)
Tubing is usually used in crude oil instrumentation system, natural gas, industrial gas, and food industry. With the involvement of the oil and gas tubing, many products would be affordable to be manufactured and the costs to convey these products to market would be economical. Products marking in the tubes include manufacture name or brand, specification number and grade on tubes. Different manufacture has different material characteristic although it is of the same grade. Thus, this research is perform to determine the modulus of elasticity, tensile strength and yield strength of stainless steel 316 from different manufactures. Comparison of modulus of elasticity, tensile strength and yield strength of stainless steel 316 from different manufactures are made. By appropriate scaling, load and displacement data that were obtained in the test were calibrated and cross-plotted to give an engineering stress-strain curve for each and every specimen. From the Universal Tensile Machine, graph of force versus displacement is generated. From the stress-strain curve, values of modulus of elasticity, ductility, tensile strength and yield strength for Sample A were 12869.22 MPa, 44.04501932%, 548 MPa, and 332.7333 MPa respectively. And for values of modulus of elasticity, ductility, tensile strength and yield strength for Sample B were 12722.43 MPa, 36.09215017%, 536.6667 MPa, and 314 MPa respectively. From the values that were obtained, the material characteristics of Sample A are found to be stronger than Sample B.